Pengaruh Model Blended learning yang Didukung Media Quizizz Terhadap Kreativitas Dan Hasil Belajar IPA Tingkat Tinggi Siswa - Thiur Dianti Siboro; Fenny Mustika Piliang; Lestina Lestina (Journal of Natural Sciences, 2022)
This study aims to determine the effect of the blended learning model supported by Quizizz media on creativity and high-level student learning outcomes. The method used in this study was a quasi-experimental (quasi-experimental) with a pretest-posttest two-group design. The population in this study were all students of Class XI MIPA SMA Foundation Higher Education Pematangsiantar for the Academic Year 2021/2022. The research sample consisted of 2 classes totaling 60 individuals, which were selected using cluster random sampling technique. The blended learning model used in this study uses Quizizz as a media to support online learning. Student creativity was measured using a questionnaire, while high-level student learning outcomes were measured using a valid and reliable descriptive test. In addition, the data obtained were analyzed using quantitative descriptive analysis by conducting analysis prerequisite tests and hypothesis testing with a significance level of 0.05. The results of this study indicate that the use of a blended learning model using quiz media has a significant effect on students' creativity with a probability value of 0.000 = 0.05 and tcount 13.189 ttable 1.701.